BANGUNAN KEAGAMAAN HINDU-BUDDHA MENURUT URAIAN KAKAWIN NAGARAKRTAGAMA - Munandar, Agus Aris (Universitas Indraprasta PGRI, 2021)
During the Majapahit era, the Nagarakrtagama book in the form of kakawin (Old Javanese poetry) was composed by Mpu Prapanca, the kakawin was completed in 1365 AD. no longer exist because it collapsed or the location is not yet known. Using an archaeological-historical approach, this study discusses several sacred buildings mentioned in the Nagarakrtagama whose existence can still be known archaeologically. The analysis was carried out by combining the written data from Nagarakrtagama with archaeological data in the form of temples on the site, to then review some of the features of the temple building. Through the analysis carried out, it can be seen that during the Majapahit era there were at least 3 types of religious buildings based on their religious background, namely Hindu-saiwa, Bauddha, and Shiva-Buddha. The most sacred buildings erected are Hindu-saiwa, it seems that in general, the Majapahit population embraces this religion. There is also a two-religious temple, namely Shiva-Buddha and a pendharmaan temple building that was erected to glorify a deceased figure, while a rare Bauddha sacred building is found in Majapahit. It seems that Buddhism did develop on a limited basis at that time.Key words: Majapahit, Hinduism, Buddha, temple, Mahameru, gods